2007
DOI: 10.1007/s10856-006-0074-1
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion and growth of vascular smooth muscle cells in cultures on bioactive RGD peptide-carrying polylactides

Abstract: The surface of poly(L-lactide) (PLLA) films deposited on glass coverslips was modified with poly(DL-lactide) (PDLLA), or 1:4 mixtures of PDLLA and PDLLA-b-PEO block copolymers, in which either none, 5% or 20% of the copolymer molecules carried a synthetic extracellular matrix-derived ligand for integrin adhesion receptors, the GRGDSG oligopeptide, attached to the end of the PEO chain. The materials, perspective for vascular tissue engineering, were seeded with rat aortic smooth muscle cells (11,000 cells/cm(2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 23 publications
4
37
0
Order By: Relevance
“…Increased adhesion of human skin fibroblasts, osteoblasts, smooth muscle cells and endothelial cells by RGD-integrin binding has been reported. 16,21,41,42 Consistent with previous studies, our results indicate that the increase in cell adhesion observed when we switched hydrophobic PLCL to hydrophilic AAc-PLCL fibrous meshes may be due to non-specific interactions. Moreover, cell adhesion was maximized on the RGDAAc-PLCL due to the synergetic effect of non-specific interactions and the specific binding of ECM molecules to their receptors.…”
Section: Resultssupporting
confidence: 91%
“…Increased adhesion of human skin fibroblasts, osteoblasts, smooth muscle cells and endothelial cells by RGD-integrin binding has been reported. 16,21,41,42 Consistent with previous studies, our results indicate that the increase in cell adhesion observed when we switched hydrophobic PLCL to hydrophilic AAc-PLCL fibrous meshes may be due to non-specific interactions. Moreover, cell adhesion was maximized on the RGDAAc-PLCL due to the synergetic effect of non-specific interactions and the specific binding of ECM molecules to their receptors.…”
Section: Resultssupporting
confidence: 91%
“…In other studies, however, both PEG and BSA have often been reported to be non-adhesive for cells and have even been used for constructing inert cell non-adhesive surfaces (for a review, see [25]). The anti-adhesive action of PEG is based on its very high hydrophilia and the mobility of its chain, which hamper stable adsorption of the proteins that mediate cell adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in vascular tissue engineering, this means that the material should enable reconstruction of the tunica intima , formed by a confluent layer of endothelial cells, and also reconstruction of the tunica media , which contain vascular smooth muscle cells. For these purposes, advanced artificial materials should not just be passively tolerated by the cells, but should act as bioactive or biomimetic, which means that they induce the required cell responses in a controllable manner (for a review, see [8,9]).…”
Section: Introductionmentioning
confidence: 99%